Clinical dilemmas in predicting the progression of pre-clinical hypertrophic cardiomyopathy—is MRI strain the solution? - Ramchand, Jay; Desai, Milind Y. (Annals of Translational Medicine, 2019)
Hypertrophic cardiomyopathy (HCM) is one of the commonest inherited cardiac diseases, with an estimated prevalence of 1 in 500 (1). It is characterized by unexplained myocardial hypertrophy, which occurs in the absence of pressure overload (e.g., hypertension, aortic stenosis) or infiltration (e.g. amyloidosis) (2,3). Myocardial hypertrophy in HCM typically occurs in the interventricular septum but can also be apical, segmental, or concentric. HCM is primarily a genetic disease involving mutations in at least 14 genes (2,4).